The Relationship between Psychological Status and Perceived Social Support among Men during Their Wives' Pregnancy - Fahimeh Sehhatie Shafaie; Mojgan Mirghafourvand; Mahbubeh Rahmati; Parviz Nouri; Amir Amir Ranjbar; Marzieh Bagherinia (Mashhad University of Medical Sciences, 2023)
Background & aim: Like becoming a mother, becoming a father is a new and important role that entails several responsibilities and expectations for men. This study aimed to investigate the relationship between psychological status and perceived social support in men during their wives' pregnancy.Methods: This cross-sectional study investigated 372 Iranian men in the third trimester of their wives' pregnancy using multistage cluster sampling from May 2014 to February 2015 in Tabriz, Iran. The self-administered questionnaires used included demographic questionnaire, Personal Resource Questionnaire (PRQ-85-part2), and short form of depression, anxiety, and stress (DASS-21). The statistical tests including Spearman correlation, Mann-Whitney, Kruskal Wallis and linear regression model were used for data through SPSS v. 21.Results:  Perceived social support was negatively correlated with anxiety (r=-0.390, P<0.001), depression (r= -0.277, P<0.001), and stress in men (r= -0.290, P<0.001). Based on the results of multiple linear regression, the father's education, mother's occupation, income, and fetus gender by ultrasound were significantly related to the anxiety of fathers. Moreover, mother's age was significantly correlated with men's depression.Conclusion: Based on the results, social support affects the psychological status of men in the third trimester of pregnancy of their wives and the levels of anxiety, depression and stress decrease in men with increasing of social support.  Healthcare providers should pay more attention to the increasing public awareness, stress management and communication skills training, and support of men during their wife's pregnancy.